2006
DOI: 10.1002/app.23468
|View full text |Cite
|
Sign up to set email alerts
|

Calix[4]arene‐filled poly dimethylsiloxane (PDMS) membranes for the pervaporative removal of benzene from dilute aqueous solution

Abstract: ABSTRACT:In this article, tert-butylcalix [4]arene (CA)-filled poly dimethylsiloxane (PDMS) membranes (CA-f-PDMS) were prepared for pervaporative removal of benzene from aqueous solution. In comparison with unfilled PDMS membrane, CA-f-PDMS membranes showed higher permselectivity towards benzene due to the inclusion interaction between benzene and CA. The separation factor increased from 3275 to 5604 when the CA content varies from 0 to 3 wt % in the PDMS membrane. On the other hand, the normalized permeation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…E P is a useful tool for understanding the PV separation properties of a hybrid membrane. Some researchers have used the relationship of the permeation flux against the feed temperature to predict the PV separation properties of membranes and have achieved fruitful results 10, 21. As reported, the E P (J/mol) value can be calculated with the following Arrhenius‐type expression:10 or where J P is the permeation flux of the component (g m −2 h −1 ), J 0 is the pre‐exponential factor, R is the gas constant (8.314 J/mol K), and T is the solution temperature (K).…”
Section: Resultsmentioning
confidence: 99%
“…E P is a useful tool for understanding the PV separation properties of a hybrid membrane. Some researchers have used the relationship of the permeation flux against the feed temperature to predict the PV separation properties of membranes and have achieved fruitful results 10, 21. As reported, the E P (J/mol) value can be calculated with the following Arrhenius‐type expression:10 or where J P is the permeation flux of the component (g m −2 h −1 ), J 0 is the pre‐exponential factor, R is the gas constant (8.314 J/mol K), and T is the solution temperature (K).…”
Section: Resultsmentioning
confidence: 99%
“…Poly(dimethylsiloxane) (PDMS) membranes filled with calixarene (CA) were reported for pervaporative removal of benzene from its dilute aqueous solution. , Compared with the unfilled PDMS membranes, those membranes filled with CA exhibited higher permselectivity toward benzene. In particular, the unusual change of permeation rate in such membranes was observed .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding permeation activation energy ( E P ) can enhance the further investigation of PV separation properties of a hybrid membrane. Some researchers used permeation flux against feed temperature to predict the PV separation properties of membranes and have achieved fruitful results 9, 18. Presently, E P (J/mol) can be calculated based on the following Arrhenius‐type expression18: or, where J P is the permeation flux of component (g/m 2 h), J 0 is the pre‐exponential factor, R is the gas constant (8.314 J/mol K), and T is the solution temperature (K).…”
Section: Resultsmentioning
confidence: 99%
“…For such purpose, various innovative techniques are newly developed. Among these, inorganic/organic hybrid is considered as one of the most effective methods to improve the permeation flux and selectivity of PV membranes 7–11. For example, Ohshima et al7 prepared a series of organic/inorganic hybrid membranes for the removal of 0.05 wt % benzene/water mixed solution, and found that hybridization of organic and inorganic moieties can increase the membrane selectivity.…”
Section: Introductionmentioning
confidence: 99%